Large Eddy Simulation Of Flow Past Road Vehicles Subjected To Pitching Oscillation - Cheng, See Yuan; Tsubokura, Makoto; Nakashima, Takuji; Okada, Yoshihiro; Nouzawa, Takahide (2011)
We examine the unsteady aerodynamic effect on pitching stability of road vehicle by large eddy simulation. To probe the vehicle's dynamic response, a forced-sinusoidal-pitching oscillation was imposed on the vehicles during the simulation. For validation purpose, we compare the numerical result with wind tunnel measurement. The simulation result shows the strong influence of unsteady flow structures around the rear end of the vehicles on their pitching stability. These flow structures include the front and rear pillar vortices and cross flow component above the trunk deck. The configuration of curved front pillar coupled with sharp-edged rear pillar produce a trend for the unsteady aerodynamic force to restrain the pitching motion, while the presence of front pillar vortices, which are associated with sharp-edge front pillar configuration, resulted in a tendency for enhancing the pitching motion.